Enthroned and Coming to Reign: Jesus’s Eschatological Use of Psalm 110:1 in Mark 14:62 - Smith, Murray J. (Journal of Biblical literature, 2022)
Many interpreters hold that Jesus’s response to the high priest (Mark 14:62), combining Ps 110:1 and Dan 7:13, refers to his imminent heavenly enthronement and says nothing of his future return. Many others recognize a reference to Jesus’s parousia but see this solely in the allusion to Dan 7:13 ("coming with the clouds"), rather than in anything drawn from Ps 110. In contrast to these views, we argue that Ps 110 provides a key to understanding Jesus’s eschatological vision in Mark. The psalm envisages a chronological distinction between the enthronement of David’s lord "at the right hand" and his eschatological victory in the world. Mark’s Jesus also, in his response to the high priest, envisages his future career in two distinct stages that mirror those set forth in the psalm: first, his enthronement at God’s "right hand," and then his final advent from heaven as the glorious Son of Man. This reading is consistent with Jesus’s teaching elsewhere in Mark, which envisages a period of bodily absence before his final return. It is supported by other early Christian texts in which the chronological progression in the psalm provides scriptural warrant for a distinction between Jesus’s present heavenly enthronement and future return.